Effectiveness of n-hexane and ethanol extract of papaya (Carica papaya L.) leaves as shallot pest (Spodoptera exigua Hübner) natural insecticide - Sari, Mery Puspita; Nugroho, L Hartanto; Sukirno, Sukirno (Jurnal Biologi Udayana, 2022)
One of the agricultural commodities that has a high selling value and consumption level is shallot (Alium ascalonicum). However, the productivity of shallots is known to be susceptible to plant-destroying organisms, such as the shallot caterpillar (Spodoptera exigua). Currently, most shallot farmers control S. exigua using synthetic insecticides. Synthetic insecticides are poisonous and use for a long time  period will cause resistance to pests and environmental pollution. One of the natural ingredients that has the potential as a botanical insecticide is papaya (Carica papaya). This study aimed to determine the effectiveness and concentration of n-hexane and ethanolic extracts of papaya leaves which are the most effective against toxicity and inhibition of the feeding power of S. exigua second instar larvae. The extract was obtained by gradual maceration of n-hexane (non polar) and ethanol (polar) solvents. Test the secondary metabolite content of papaya leaves using Thin Layer Chromatography (TLC). The results showed that the ethanol extract was the most effective extract in causing toxicity to larvae with the highest percentage of 96.67%. Meanwhile, n-hexane extract was more effective in inhibiting larval feeding than ethanol extract with the lowest feeding area of 2,27 mm. The most effective concentration of against toxicity and feeding inhibition of larvae is concentration 3%. The LC 50 value of the ethanol extract was 0.0207% and the n-hexane extract was 0.0459%. Both extracts are known to contain compound groups, namely tannins, terpenoids, flavonoids, and alkaloids.